Dual High Flow Oxygen Therapy and CPAP Ventilation in a Single Device for COVID-19 - Kelly, James; Dowe, Michael; Briggs, Jonathan; Chan, Michael; Martin-Lazaro, Juan (British Journal of Healthcare and Medical Research, 2020)
High flow oxygen therapy (HFOT) and Continuous positive airway pressure (CPAP) could be considered the most important ventilatory therapies during the COVID-19 pandemic because of their frequency of use. There are many devices on the market which provide this type of ventilatory support, and these should be distinguished from one another by their efficacy, versatility, patient comfort, hygiene and cost. We evaluated the AquaVENT FD140i from Armstrong Medical, which delivers both HFOT and CPAP, concluding that it provides two potentially efficacious treatments to COVID-19 patients, while its long-life battery facilitates transfers for escalation and de-escalation of care. We compared the AquaVENT FD140i with the Fisher & Paykel MR850, which is a gold standard in the market. We also looked at the compatibility of their humidifier and disposables with Armstrong Medical devices. The results of this study suggest the compatibility of both systems, which has the potential to reduce consumable costs.